ByzRev 08.2026.007: Geoffrey Greatrex, Procopius of Caesarea: the Persian Wars. Translation, with introduction and notes.: A historical commentary. Cambridge – New York: Cambridge University Press 2022. - Turquois, Elodie (The Byzantine Review, 2026)
Geoffrey Greatrex, Procopius of Caesarea: the Persian Wars. Translation, with introduction and notes. Cambridge -- New York: Cambridge University Press 2022. 300 pp. – ISBN 978-1-10-716570-0 – Geoffrey Greatrex, Procopius of Caesarea: the Persian Wars. A historical commentary. Cambridge – New York: Cambridge University Press 2022. 800 pp. – ISBN 978-1-107-05322-9